Speech Development of a Person in the Context of Language Space (Texas Journal of Philology, Culture and History, 2023)
the influence of the communicative space on the speech development of the individual is revealed. The main reason that creates a barrier to understanding the culture of speech among students is the deliberate distortion of the language, the language game, the use of slang, which leads to a closure in social, intellectual, and speech development.